Comparative Anatomy and Morphology of the Leaves of Grenache Noir and Syrah Grapevine Cultivars - Gago, P.; Conejero, G.; Martínez, M.C.; This, P.; Verdeil, J.L. (South African Journal of Enology and Viticulture, 2019)
Grenache Noir and Syrah are two of the grapevine (Vitis vinifera L.) cultivars used to a great extent worldwide. They have very different leaf morphologies from an ampelographic (botanical) point of view. This might also be related to differences in the anatomy and micro-morphology of their leaves. The goal of the present work was to compare these cultivars’ leaf anatomy and morphology. Adult leaves from both cultivars were characterised using a range of microscopy techniques. Grenache Noir had a significantly smaller leaf surface area, but a significantly thicker leaf blade, than Syrah. It also had significantly larger stomata and a larger stomatal index than Syrah. The distribution of mesophyll tissues was similar in both cultivars, but the upper epidermis was significantly thicker in Grenache Noir, and the palisade parenchyma cells were longer in Syrah. The mesophyll tissues of both cultivars contained abundant idioblasts carrying crystals of calcium oxalate and mucilage. This work reveals quantitative and qualitative differences in the anatomy and morphology of mature Grenache Noir and Syrah leaves. Further work is needed to determine how these anatomical and morphological differences may be connected with different responses at the functional level.